Theoretical and Practical Issues of Sexual Crimes Against Children - Oleksandr I. Motliakh; Yevhen Korzh; Nadiia Stasiuk; Leonid Shcherbyna; Yana Lutsenko (Universitas Negeri Semarang, 2025)
This study investigates sexual crimes against children with the aim of identifying legislative, psychological, and institutional mechanisms for prevention and response. Sexual violence against minors remains a persistent problem in Ukraine and globally, with high latency and complex causes that demand multidimensional analysis. The research applies a normative legal approach combined with dialectical and general scientific methods (analysis, synthesis, induction, generalization), supported by specialized psychological and forensic techniques. Results highlight the juridical, philosophical, and sociological objectives of legal protection of children, the challenges of applying polygraph examinations to minors, and the controversial role of medical measures such as chemical castration. The study underscores the significance of the Unified Register of Child Sex Offenders as a practical tool for prevention. The article demonstrates that combating sexual crimes against children requires a comprehensive strategy that integrates legal reforms, psychological support, medical interventions, and international best practices. The Ukrainian experience during wartime conditions adds urgency and uniqueness to this study.